RAPID SURVEYS REVEAL HEALTHY CORAL-SPONGE COMMUNITIES ON KRAKATAU REEFS - Singgih Afifa Putra (BERITA BIOLOGI, 2020)
The Krakatau Islands in the Sunda Strait have been significantly impacted by catastrophic volcanic eruptions in 1883 and 2018. The marine habitats are not well studied, neither in the past nor in the present. This research is a report on the distribution and ecology of corals and sponges in the Krakatau Volcanic Complex at the three islands of Anak Krakatau, Rakata, and Panjang. This study used 100 m transects long in 5–7 m depth. Hard coral and soft coral communities are found to live with a coverage varied between 25-53% and 0-24%. Dead coral skeletons covered 14–40% of the surveyed area and did not seem to affect the abundance of sponges recorded. The Sponges occupied 0–6% of the area, and they often acted as coral competitors, shaping the benthic ecosystems. The recorded sponges only belong to the Demospongiae class, which are the Suberitid species that are commonly found in Indonesian waters, e.g., Amorphinopsis excavans, Protosuberites collaris, and Terpios sp. The excavating sponge Cliona cf. orientalis was frequently found to be a successful competitor of massive Porites sp., aggressively overgrowing live parts of the coral. Two Haliclona species and Mycale relicta colonized dead coral skeleton. Overall, the benthic communities appear healthy and are comparable to other similar locations that are not affected by volcanic activity.